2015
DOI: 10.1007/s10856-015-5535-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cell-wall damage mediated, antibacterial activity of core–shell ZnO@Ag heterojunction nanorods against Staphylococcus aureus and Pseudomonas aeruginosa

Abstract: Hybrid ZnO@Ag core-shell nanorods have been synthesized by a synthetic strategy based on seed mediated growth. Formation of core-shell nanostructures was confirmed by UV- diffused reflectance spectroscopy (UV-DRS), X-ray diffraction studies, field emission scanning electron microscopy and high resolution transmission electron microscopy. UV-DRS analysis of hybrid core-shell nanorods suggests the possibility of interfacial electron transfer between surface anchored Ag nanoclusters and ZnO nanorods. Successful d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…However, the zones of inhibitions produced against A. flavus, A. terreus, and L. theobromae were comparable with standard antibiotic drugs but did not exceed. FDNP-induced inhibition of P. syringae is comparable with chemically synthesized Ag:ZnO NPs [63], and it can be attributed to the provisioning of larger surface area of FDNPs toward microbial contact. Studies have supported the effectiveness of combining NPs with antibiotic drugs, and their synergistic effects were commendable [64].…”
Section: Resultsmentioning
confidence: 74%
“…However, the zones of inhibitions produced against A. flavus, A. terreus, and L. theobromae were comparable with standard antibiotic drugs but did not exceed. FDNP-induced inhibition of P. syringae is comparable with chemically synthesized Ag:ZnO NPs [63], and it can be attributed to the provisioning of larger surface area of FDNPs toward microbial contact. Studies have supported the effectiveness of combining NPs with antibiotic drugs, and their synergistic effects were commendable [64].…”
Section: Resultsmentioning
confidence: 74%
“…The high amount of Ag leads to a higher OD 260 . It is demonstrated that nano Ag is beneficial to break the cell membrane 73 . Moreover, the destructive speed for S. putrefaciens is is faster than P. aeruginosa , which may be because of the different structure and thickness of the two bacterial membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Silver nanoparticles with an average size of about 7 nm were designed on heterojunctions at the surface of the ZnO nanorods. The probable mechanism derives from the generation of reactive oxygen species due to electron transfer between zinc oxide nanorods and silver nanoclusters which triggers physical destruction of the bacterial cell wall [74].…”
Section: Antibacterial Activity Of Core-shell Nanoparticlesmentioning
confidence: 99%